Lyme borreliosis [ biology, epidemiology, and control - Gray, J. [ (Jeremy S.)] (CABI Publishing, 2002)
This book contains 12 chapters. The first chapter outlines the historical and clinical aspects of Lyme borreliosis including descriptions of the disease in humans and domestic animals, and of diagnosis and treatment. The second chapter deals with ecologl methods and terminology and chapters 3-5 describe the biology of the spirochaetes and their behaviour in vectors and vertebrates. The next 4 chapters (6-9) concern the ecology of Borrelia burgdorferi in Europe, Russia, South East Asia and North America, and the last 3 chapters (10-12) deal with the application of the biological and ecological attributes of the pathogens to disease epidemiology, vaccine development and ecological management of Lyme borreliosis